2022
DOI: 10.3390/cells11071205
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-Mediated Autophagy in Neurodegenerative Diseases and Acute Neurological Insults in the Central Nervous System

Abstract: Autophagy is an important function that mediates the degradation of intracellular proteins and organelles. Chaperone-mediated autophagy (CMA) degrades selected proteins and has a crucial role in cellular proteostasis under various physiological and pathological conditions. CMA dysfunction leads to the accumulation of toxic protein aggregates in the central nervous system (CNS) and is involved in the pathogenic process of neurodegenerative diseases, including Parkinson’s disease and Alzheimer’s disease. Previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 153 publications
0
10
0
Order By: Relevance
“…Thus, autophagy activation is recently emerging as a hot topic to study neuroprotective mechanisms in chronic retinal neurodegenerative disorders (Kaarniranta et al, 2022). Similarly, given the parallelism between traumatic and chronic degenerative conditions, the activation of autophagy in the course of traumatic CNS injury is thought to produce a strong activation to elicit functional and anatomical recovery (Movahedpour et al, 2022;Zhang et al, 2022;Filippone et al, 2022;Xu et al, 2022;Kanno et al, 2022). This is partly based on the induction of stem cells (Xu et al, 2021;Maiti et al, 2019;Ceccariglia et al, 2020;Hwang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, autophagy activation is recently emerging as a hot topic to study neuroprotective mechanisms in chronic retinal neurodegenerative disorders (Kaarniranta et al, 2022). Similarly, given the parallelism between traumatic and chronic degenerative conditions, the activation of autophagy in the course of traumatic CNS injury is thought to produce a strong activation to elicit functional and anatomical recovery (Movahedpour et al, 2022;Zhang et al, 2022;Filippone et al, 2022;Xu et al, 2022;Kanno et al, 2022). This is partly based on the induction of stem cells (Xu et al, 2021;Maiti et al, 2019;Ceccariglia et al, 2020;Hwang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also indicated that chaperon-mediated autophagy (CMA), which is inhibited by RARα, is activated by BT382 without inhibiting macroautophagy ( Anguiano et al, 2013 ; Gomez-Sintes et al, 2022 ). CMA activation, which shows neuroprotection in neurodegenerative diseases and acute neurological insults ( Cuervo and Wong, 2014 ; Kanno et al, 2022 ), may be related to the neuroprotective effects of BT382 against P7 ethanol toxicity. Presently, we have not studied the long-term effects of BT382, partly because we expect that once initial apoptotic neurodegeneration is blocked, subsequent glial activation and GABAergic cell loss would be also blocked, as indicated in our previous studies using lithium ( Sadrian et al, 2012 ; Lewin et al, 2018 ; Saito et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy plays a major role in many diseases, including immune diseases [ 35 , 36 ], neurodegenerative diseases [ 37 ], atherosclerosis [ 38 ], and cancers [ 39 , 40 ]. Our present work suggests that autophagy may also have a role in eosinophilic asthma.…”
Section: Discussionmentioning
confidence: 99%